The Operational Present of Sensibility - Hansen, Mark B.N. (The Nordic Journal of Aesthetics, 2016)
Contemporary digital technologies afford unprecedented access to levels of temporal experience that have long remained beyond the scope of human thematization. In their efforts to historicize these affordances, historians of science have insisted on the peculiarity of this access, the fact that it does not take place through any direct expansion of human perceptual capacities, but rather through a human-machine assemblage that supplements perception by putting it into systemic co-relation with a technical operationality whose “content” perception cannot access. In this article, Hansen utilizes this indirect model of the temporal expansion of human agency to explore contemporary micro-computational expansion of sensibility, both as it informs data capitalism and efforts to counter the latter’s sway.